Wireless university accessibility systems - Mohd Nordin, Mohd Kamarul Azli (2007)
For century, most of office and institution used traditional method to check the access authorization of individuals to buildings. This method is proved successful in order to prevent any unwanted intruder but it sometime waste time especially during peak time. Besides it used many man powers to do it. Lately, a very valuable technology called Radio Frequency Identification (RFID) is introduced. RFID is a new technology that incorporates the use of electromagnetic or electrostatic coupling in the radio frequency (RF) portion of the electromagnetic spectrum to uniquely identify an object, animal, or person. The basic idea behind of this technology is to unravel the problem of traditional method by using a card which contains data of user. This card can be easily read by a reader then gives access to enter the building. In this project, a RFID reader will be integrated with Microcontroller 68HC11 where the microcontroller will control the whole system. The project is applied to entrance of university gate which require access before the gate will automatically open. If there any card is attached, the RFID reader will send data to microcontroller and the microcontroller will indentify if the user is staff, student or outsider. This system can prevent any unwanted intruder from entering the building. -Author